EFFICACY OF KINESIO TAPING ALONG WITH DROP SQUAT EXERCISES VERSUS KINESIO TAPING ALONG WITH LEG EXTENSION EXERCISES ON PAIN AND MUSCLE STRENGTH AMONG VOLLEYBALL PLAYERS – A COMPARATIVE STUDY (Cuestiones de Fisioterapia, 2025)
Background: Jumper’s knee is a clinically diagnosed condition of activity related to the anterior knee painassociated with tenderness at the inferior pole of the patella where the patellar tendon attaches. The prevalence ofthis condition in elite volleyball players and basketball players has been found to be over 40 percent. Mostcommon symptoms of Jumper’s knee are pain, tenderness, and stiffness around the joint and pain is occurringwith varying intensities. The study’s primary objective was to find out the Efficacy of Kinesio taping along withDrop squat exercises and Kinesio taping along with Leg extension exercises on pain and muscle strength amongvolleyball players.